Opposing perspectives on the drone debate - Strawser, Bradley Jay; Hajjar, Lisa.; Levine, Steven; Naqvi, Feisal H.; Witt, John Fabian; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
In this book, five scholars square off in a lively debate over the ethics of drones and their contentious use.
Keywords: Political science; International relations; Politics and war; Terrorism; Political violence